The making and remaking of China's "red classics" : politics, aesthetics, and mass culture - Roberts, Rosemary A.; Li, Li, 1957 July 21- (Hong Kong University Press, 2018)
The Making and Remaking of China's "Red Classics" is the first full-length work to bring together research on the "red classics" across the entire Maoist period through to the reform era. It covers a representative range of genres including novels, short stories, films, TV series, picture books, animation, and traditional-style paintings. Collectively, the chapters offer a panoramic view of the production and reception of the original "red classics" and the adaptations and remakes of such works after the Cultural Revolution. The contributors present fascinating stories of how a work came to be